A Case of Access: Inuvialuit Engagement with the Smithsonian's MacFarlane Collection (Project Summary) - Kate Hennessy; Natasha Lyons (Simon Fraser University, 2014)
The project summary from "A Case of Access", an IPinCH Community Initiative.